Diagnosis of temporomandibular joint (TMJ) ankylosis in children - Priya Shetty; Ann Thomas; B Sowmya (Wolters Kluwer Medknow Publications, 2014)
Temporomandibular joint (TMJ) ankylosis involves fusion of the mandibular condyle with the base of the skull. It results in functional, esthetic, and psychosocial limitations, if it affects children at an early age. Hence, it is important to recognize and diagnose the pathology and provide immediate treatment alternatives to improve the patient condition. In this case report, we highlight the diagnostic perspective of TMJ ankylosis in children, and the use of 3D computed tomography as an effective diagnostic aid.